Pengembangan POTRAME: Media Pop-Up Book Berbasis Augmented Reality Bermuatan Budaya Lokal Jajanan Tradisional Khas Nusantara untuk Pembelajaran Bangun Ruang di SMP Negeri Kota Semarang - Fatmadewi, Elisa Mutiara; Syakir, Faiza Jasmine; Putri, Verda Chamelia; Fadillah, Adinda Cahya; Pambudi, Fawwaz Haryolukito; Dewi, Nuriana Rachmani (Jurnal Penelitian dan Pembelajaran Matematika, 2025)
This study aimed to design and develop an innovative learning medium called POTRAME (Pop-Up Book with Augmented Reality) that incorporates local cultural elements of traditional snacks as a supporting tool for teaching solid geometry in junior high schools. The development was motivated by findings indicating students’ low ability to visualize three-dimensional shapes, which leads to poor mathematical understanding, as well as the limited availability of instructional media capable of connecting mathematical concepts to local cultural contexts familiar to students’ daily lives. The research employed the ADDIE development model, focusing on the development stage. The resulting product was validated by material experts, media experts, and practitioners through questionnaires, interviews, and observations. The validation results indicated a very high level of feasibility: 94.89% from the material expert, 93.07% from the media expert, and 94.91% from the practitioner. Suggestions for improvement included adding citation sources, refining pop-up visual details to appear more realistic, and strengthening the integration of deep learning principles to foster higher-order thinking skills. Based on these results, POTRAME was declared feasible for use as a contextual, interactive, and culturally relevant learning medium, potentially enhancing students’ understanding of solid geometry concepts at the junior high school level.